New Histogram Equalization Based Detail And Brightness Preserving Techniques For Digital Images - Ooi , Chen Hee (2010)

(untitled)
Although Histogram Equalization (HE) is widely used as a contrast enhancement method because of its effectiveness and simplicity, it tends to produce mean brightness change, intensity saturation problem and noise amplification. Therefore, two novel brightness preservation methods, namely Brightness Preserving Plateau Limit Histogram Equalization (BPPLHE) and Quantized Plateau Limit Bi-Histogram Equalization (QPLBHE) are proposed. The method for preserving mean brightness is under a very high demand, especially where consumer electronic products are concerned, like the television, monitor etc.